PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DENGAN MENGGUNAKAN PENDEKATAN PEMBELAJARAN KOOPERATIF TIPE LISTENING TEAM(LT) - ADIWANGSA, RAFIKA RAHMAWATI (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Learning conditions in primary school (elementary) education especially Citizenship (Civics) learning is learning process in class IV shows the low active student involvement, students are rarely asked about the subject matter. In addition, students quickly feel tired and not concentrating on learning because the teacher is not following the approach can stimulate the activity of students. This happens constantly so that the learning outcomes of students who obtained low. For that researchers using Cooperative Learning Type Listening Team (LT) to improve student learning outcomes. This Research use Approach qualitative and is quantitative, while research type that is Research of Action Class PTK with research device cover, (1) planning, (2) execution, (3) perception, and (4) refleksi. Learning used is Cooperative Learning Approach Listening Study Team (LT) and consists of cycle I and cycle II. Student learning outcomes increased from an average of 76.99 to 85.09 at cycle II.   Kata Kunci: pembelajaran Pkn, listening team, hasil belajar